ANALYSIS OF TOURIST POTENTIAL FOR THE DEVELOPMENT OF HEROIC-PATRIOTIC TOURISM IN THE CARPATHIAN REGION OF UKRAINE - PANKIV, Natalia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
In the current conditions of the war in Ukraine, when the country is at the cost of living and the efforts of the Ukrainian military, volunteers, volunteers defend freedom and territorial integrity, national-patriotic education becomes a priority. Therefore, in this article, we have analyzed the main types of resources used in the organization of heroic and patriotic tours in the Carpathian region of Ukraine and their importance for the patriotic education of youth. Lviv region belongs to the regions of Ukraine where there are the most favorable opportunities for the development of heroic and patriotic tourism. The region has a significant number of heroic and patriotic resources, in total, more than 170. Among all types of heroic and patriotic resources, the largest share is occupied by monuments and memorial sites associated with prominent figures of the national liberation struggle, burials are in the second places, monuments and memorials associated with significant historical events and their participants occupy the third position, museums and museum exhibits occupy the fourth position and military infrastructure (hiding places) in number are in fourth place. Transcarpathia, given the historical peculiarities of its formation, also has significant resources for the development of heroic and patriotic tourism. The treasury of cultural heritage of the Transcarpathian region includes monuments of archeology, history, architecture, and monumental art. Ivano-Frankivsk region also has a large number of material and spiritual monuments, including museums. According to research, about 170 objects of heroic and patriotic tourism have been identified in the region. Chernivtsi region also has a large number of museums and memorial sites associated with the life and work of prominent figures of science and culture of Bukovina and Europe. Burials and museums are important among the heroic and patriotic resources of Bukovina. In total, more than 600 tourist sites have been discovered in the Carpathian region, among which the most numerous are burials and monuments, and memorial sites associated with significant historical events and their participants. In particular, museums and military infrastructure are of great interest to tourists, the largest number of them were found in Lviv and Ivano-Frankivsk regions.
Keywords: national-patriotic education; heroic-patriotic tourism; tourist resources; Carpathian region